STAD Type Learning as an Alternative Form in Order to Improve the Quality of Accounting Learning - Listiadi, Agung (International Journal of Educational Research & Social Sciences, 2024)
Education is a universal activity. Wherever and whenever in this world education is seen as a human activity to humanize humans themselves, namely so that humans are cultured. Even though education is a universal or general phenomenon in every social life, the differences in the views of life adopted by each community and even individuals cause differences in carrying out these educational activities. Along with the progress of today's era which is so rapid, various efforts to improve the education system and its devices are continuously being made. One way that can be done to improve the quality of Studying is to use various interesting alternative Studying models, especially in accounting Studying, one of which is by using the Students Team Achievement Division (STAD) type Studying model. Students activity during the application of the STAD type cooperative Studying model to financial accounting material was very good. This can be seen from the increase in the average value of Students activity during the Studying process.